The lectin-like domain of thrombomodulin ameliorates diabetic glomerulopathy via complement inhibition - Wang, Hongjie; Bock, Fabian; Kashif, Muhammed; Bierhaus, Angelika; Nawroth, Peter Paul; Kirschfink, Michael (Thrombosis and haemostasis, 2012)
Coagulation and complement regulators belong to two interactive systems constituting emerging mechanisms of diabetic nephropathy. Thrombomodulin (TM) regulates both coagulation and complement activation, in part through discrete domains. TM’s lectin like domain dampens complement activation, while its EGF-like domains independently enhance activation of the anticoagulant and cytoprotective serine protease protein C (PC). A protective effect of activated PC in diabetic nephropathy is established. We hypothesised that TM controls diabetic nephropathy independent of PC through its lectin-like domain by regulating complement. Diabetic nephropathy was analysed in mice lacking TM’s lectin-like domain (TMLeD/LeD) and controls (TMwt/wt). Albuminuria (290 μg/mg vs. 166 μg/mg, p=0.03) and other indices of experimental diabetic nephropathy were aggravated in diabetic TMLeD/LeDmice. Complement deposition (C3 and C5b-9) was markedly increased in glomeruli of diabetic TMLeD/LeDmice. Complement inhibition with enoxaparin ameliorated diabetic nephropathy in TMLeD/LeDmice (e.g. albuminuria 85 μg/mg vs. 290 μg/mg, p <0.001). In vitroTM’s lectin-like domain cell-autonomously prevented glucose-induced complement activation on endothelial cells and -notably -on podocytes. Podocyte injury, which was enhanced in diabetic TMLeD/LeDmice, was reduced following complement inhibition with enoxaparin. The current study identifies a novel mechanism regulating complement activation in diabetic nephropathy. TM’s lectin-like domain constrains glucose-induced complement activation on endothelial cells and podocytes and ameliorates albuminuria and glomerular damage in mice.
30.November 2017 (online)
Gesehen am 14.02.2019